Playing: Christian Explorations of Daily Living/ Religions in Play: Games, Rituals and Virtual Worlds - Collins, Michael F. (Implicit religion, 2013)
The article reviews the books "Playing: Christian Explorations of Daily Living" by James H. Evans Jr. and edited by David H. Jensen and "Religions in Play: Games, Rituals and Virtual Worlds" edited by Philippe Bornet and Maya Burger.